On the correlation between the fast solar wind flow changes and substorm occurrence. Issue 13 (14th July 2015) - Semenov, V. S.; Kubyshkina, D. I.; Kubyshkina, M. V.; Kubyshkin, I. V.; Partamies, N.
Abstract There is a point of view that solar wind factors, which break the magnetotail symmetry, are more effective in triggering the magnetospheric substorm. To clarify the question we use a database of substorm onsets and found the evident dependence of the substorm probability on the solar wind flow direction jumps (asymmetric factor), while distribution of the substorm occurrence on the solar wind number density jumps (symmetric factor) is homogeneous. The theoretical interpretation is based on the extension of the existing symmetric Kan model for a bent current sheet. Allowing the model tilt angle to vary in time, we found that the induced electric field penetrates to the central region of the bent current sheet. If the solar wind direction jump increases the bending, then induced electric field thins the current sheet and thus stimulates the reconnection. In the opposite case the current sheet thickens. We claim that this effect is sufficient (provides twice or more thinning of the current sheet in 10 min).